1983
DOI: 10.1007/bf02907770
|View full text |Cite
|
Sign up to set email alerts
|

On the occurrence of α-acetolactate decarboxylases among microorganisms

Abstract: The ability to generate r decarboxylase activity has been detected among bacteria but not among members of any other group of microorganisms. Among bacteria found to produce an :t-acetolactate decarboxylase several, such as strains of Bacillus and Lactobacillus, are potential sources of decarboxylases which may be applied in brewing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…However, the practical use of this procedure is complicated by a limited stability of the Aerobacter ct-acetolactate decarboxylase at the pH of beer (7). A search for an enzyme with higher stability in the acid pH region led, among others (7,8,10), to an a-acetolactate decarboxylase in a strain of Lactobacillus casei which met this criteria (8,9). This enzyme removed as expected all ct-acetolactate from freshly fermented beer within 48 hrs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the practical use of this procedure is complicated by a limited stability of the Aerobacter ct-acetolactate decarboxylase at the pH of beer (7). A search for an enzyme with higher stability in the acid pH region led, among others (7,8,10), to an a-acetolactate decarboxylase in a strain of Lactobacillus casei which met this criteria (8,9). This enzyme removed as expected all ct-acetolactate from freshly fermented beer within 48 hrs.…”
Section: Introductionmentioning
confidence: 99%
“…Enzymes with the ability to decarboxylate ct-acetolactate are widely found amoung bacterial strains but not in other groups of microorganisms (7,8,10). The only ct-acetolactate decarbo~ylase (EC 4.1.1.5.)…”
Section: Introductionmentioning
confidence: 99%
“…Godtfredsen et al, however, find the natural function of ALDC a matter of speculation (10) In 1972, Collins (3) suggested that the presence of ALDC may cause auxotrophy for valine and panthotenic acid as a (17) and aldB of B. brevis (this work). Eighty-five identical amino acids are marked (*).…”
Section: Discussionmentioning
confidence: 75%
“…Among the various bacterial species found to generate acetolactate decarboxylase activity (6) some are, a priori, quite promising sources of decarboxylases for application in industrial brewing. Species of Bacillus licheniformis found to generate the decarboxylase are thus widely applied for production of various food-grade enzymes and a large number of lactic acid Abbreviations: DSM = Deutsche Sammlung von Microorganismen, EBC = European Brewery Convention.…”
Section: Introductionmentioning
confidence: 99%